Intensive reading with literature text in the EFL classroom for developing the Intercultural Competence - Chancay Cedeño, Carlos Humberto (Revista Ecos de la Academia, 2021)
This study aims to develop the Intercultural Competence (IC) through intensive reading using literature texts. It was developed in the School of Language Teaching of the Faculty of Philosophy, Literature and Sciences of the Education at Universidad Técnica de Manabí, concretely with the students of the first semester. The study consisted of including an intensive reading technique to reading a literature masterpiece from William Shakespeare called The Tempest to analyse the cultural context of the story and contrast it with the local culture. With this, it was intended that students can establish similarities and differences between the local culture and the context of the story. Also, students clarified stereotypes that had formed throughout the reading. In conclusion, the students’ interest in differentiating the facts of the story with everyday situations within the Ecuadorian context could be observed. Likewise, the stories could be related to events that occurred in other regions of Latin America. On the other hand, this process helped to increase the vocabulary and fluency to talk about daily situations related to the stories read in the classroom and therefore, to develop intercultural competence.